Air pollution modelling for birth cohorts: a time-space regression model. Issue 1 (December 2016) - Proietti, Elena; Delgado-Eckert, Edgar; Vienneau, Danielle; Stern, Georgette; Tsai, Ming-Yi; Latzin, Philipp; Frey, Urs; Röösli, Martin
Abstract Background To investigate air pollution effects during pregnancy or in the first weeks of life, models are needed that capture both the spatial and temporal variability of air pollution exposures. Methods We developed a time-space exposure model for ambient NO2 concentrations in Bern, Switzerland. We used NO2 data from passive monitoring conducted between 1998 and 2009: 101 rural sites (24, 499 biweekly measurements) and 45 urban sites (4350 monthly measurements). We evaluated spatial predictors (land use; roads; traffic; population; annual NO2 from a dispersion model) and temporal predictors (meteorological conditions; NO2 from continuous monitoring station). Separate rural and urban models were developed by multivariable regression techniques. We performed ten-fold internal cross-validation, and an external validation using 57 NO2 passive measurements obtained at study participant's homes. Results Traffic related explanatory variables and fixed site NO2 measurements were the most relevant predictors in both models. The coefficient of determination (R2 ) for the log transformed models were 0.63 (rural) and 0.54 (urban); cross-validation R2 s were unchanged indicating robust coefficient estimates. External validation showed R2 s of 0.54 (rural) and 0.67 (urban). Conclusions This approach is suitable for air pollution exposure prediction in epidemiologic research with time-vulnerable health effects such as those occurring during pregnancy or in the first weeks of life.